Variability of Material Solutions for the Perimeter Walls of Buildings in Post-Industrial Settlements as Part of Energy Rehabilitation and Achieving Carbon Neutrality - Hamed Afsoosbiria; Darja Kubečková; Oskar Kambole Musenda; Khaled Mohamed (Energies)
Post-industrial sites are a part of many cities. The impacts of industrial activities are not only evident in the area where the activity took place, but also affect the buildings within these areas. Buildings that served the industry in the past were built mainly by mass construction methods. From today’s point of view, these buildings are unsatisfactory in terms of typology, operation, and energy. In particular, energy rehabilitation is a way to restore industrial buildings and bring them to a full-fledged state. This issue is documented in a case study of a city affected by underground mining activity and on a selected skeleton construction. Given that industrial buildings have heavy or mass structures where some elements like beams and columns are damaged, it is crucial to consider not only energy solutions, but also the structural and architectural aspects of these buildings. In terms of thermal engineering and energy, including the renovation of structures, a software-supported evaluation of three material variants for the envelope walls of the skeleton construction from the 1970s was conducted. This study evaluates the thermal performance of conventional, proposed, and traditional wall designs by analysing their U-values, thermal resistance, and structural advantages. The results reveal that the conventional wall, featuring a 150 mm EPS 70 NEO insulation layer, achieves the lowest U-value, outperforming the proposed wall by a factor of 1.2 in thermal resistance. Both designs significantly reduce U-values compared to traditional walls, by factors of 6.55 and 5.40, respectively. Despite a 23% reduction in thickness relative to the conventional wall (and 44% compared to traditional walls), the proposed wall demonstrates robust thermal performance. Further benefits include reduced structural dead load, with the conventional and proposed walls being 3.70 times lighter per square meter than traditional walls. This reduction can decrease foundation, column, and beam dimensions, optimizing building design. Thermal bridging analysis highlights superior corner insulation in conventional walls due to higher surface temperatures, while the proposed wall maintains effective insulation with surface temperatures close to indoor conditions. Overall, the findings underscore the importance of advanced materials in achieving efficient thermal performance while balancing architectural and structural demands. The results achieved from the experimental work show that industrial buildings can be effectively energy-renovated in a way that complies with legislative documents, successfully extends the physical life of the frame structures, and contributes to carbon neutrality.